Representasi Kekerasan Dalam Ranah Keluarga Terhadap Tokoh Perempuan Dalam Film Rumah Untuk Alie - Aisiyah, Elsa Tri; Sudrajat, Arief; Ridwan, Ahmad (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2026)
Whitin the family sphere, violence against women remains a significant social problem that is frequently treated as a private matter. As a cultural medium, film plays an important role in shaping public understanding of such issues through processes of representation. This study applies Stuart Hall’s theory of representation to identify the forms of domestic violence experienced by the female protagonist and to analyze how these forms are depicted in the film Rumah untuk Alie (released 17 April 2025). Using a descriptive qualitative approach and semiotic content analysis, the research draws on primary data from the film and secondary data from books, academic journals, and official reports on violence against women. Data were collected through repeated observation of scenes and documentation of dialogues and visual details. The findings indicate that the film represents three main forms of domestic violence: physical, verbal, and emotional/psychological. Through its narrative structure, dialogue patterns, and visual framing, the film highlights the marginalization of women and demonstrates how violence is embedded within unequal power relations in a patriarchal household. At the same time, the film positions domestic violence both as a normalized family practice and as a critique of broader social structures. Overall, the study underscores that such representations help reveal domestic violence as a structural social issue rather than an individual or private concern.